Composite structure in the Kutus-kutus factory building, Gianyar, Bali - Ni Putu Indah Puspita Anggraeni; I Nengah Sinarta; I Putu Ellsa Sarassantika (Journal of Infrastructure Planning and Engineering, 2022)
This study focuses on the design implementation and performance analysis of concrete-steel composite structure of a four-story Kutus-Kutus Factory, a facility for the production of herbal oils, built in the seismically active Gianyar district of Bali. In order to create an efficient, fully composite cross section, the design process uses an analytical approach that emphasizes the relationship between the concrete slab and steel beams as well as the design of each of these components. The structure was designed and assessed in accordance with Indonesia Building Standard guidelines for minimum load, earthquake-resistant, and concrete and steel based material requirements. The final results of the design confirmed that the composite performance is strong enough to withstand enormous loads combined in industrial buildings, particularly in seismically active areas, and can operate within the recommended safety margins and restrictions. This paper ends with a call for more research on the real application of composite structure design in Indonesia, which can then assist the rapidly expanding Indonesian construction industry in maximizing the advantages of using composite construction techniques.